Endpapers : a novel - Kelly, Jennifer Savran, 1974- (Algonquin Books of Chapel Hill, 2023)
"In 2003 New York, a genderqueer book conservator who feels trapped by her gender presentation, ill-fitting relationship, and artistic block discovers a decades-old hidden queer love letter and becomes obsessed with tracking down its author"--